Source and frequency of dry season lipid supplementation of grazing, finishing cattle - Santana, Marcia Cristina Araujo; Vieira, Bruno Ramalho [UNESP]; Costa, Diogo Fleury; Dian, Paulo Henrique Moura; Fiorentini, Giovani [UNESP]; Canesin, Roberta Carrilho [UNESP]; Pereira, Gener Tadeu [UNESP]; Reis, Ricardo Andrade [UNESP]; Berchielli, Telma Teresinha [UNESP] (Csiro Publishing, 2015)
The objective of this study was to evaluate the effects of sources of soybean oil [ground soybean (GS), soybean oil (SO) and calcium salts of soybean oil (CS)] on DM intake (DMI), ingestive behaviour and average daily gain (ADG) of heifers grazing marandu palisadegrass (Brachiaria brizantha cv. Marandu) supplemented in two frequencies [daily and 3 days a week (Monday, Wednesday and Friday - MWF)]. The experiment was conducted from July until November of 2007. Forty-two crossbred heifers (1/4 Nellore x 1/4 Santa Gertrudis x 1/2 Braunvieh), 17-months old and 297.1 kg +/- 30.5 BW +/- s.e.m., were used. Supplements were offered at 0.75% BW.day. Treatments were allocated in a completely randomised design and distributed in a factorial arrangement (3 x 2 - SO from three different sources and two supplementation frequencies). Total DMI was greater in August and October (2.2 kg DM/kg BW) than in November (1.5 kg DM/kg BW). There was an effect of SO source on total DM, herbage and nutrients intake, but no effects of supplementation frequency. The animals supplemented with SO had greater DMI (P < 0.05) than the ones fed GS and CS. Average daily gain (0.580 g) was not affected by supplement sources or feeding frequency. Therefore, GS and CS are more efficient supplements. Supplementation frequency altered grazing time differently according to source. The MWF treatment resulted in a decreased grazing time when GS and SO were fed. However, in days when supplements were not offered, grazing time was increased for GS and CS. It was concluded that a decreased frequency of supplementation may be implemented without effect on weight gain and will reduce labour and machinery costs.
Keywords: Brachiaria brizantha; Calcium salts; Performance; Soybean